2013
DOI: 10.1037/a0028350
|View full text |Cite
|
Sign up to set email alerts
|

The force of law: The effects of sexual orientation antidiscrimination legislation on interpersonal discrimination in employment.

Abstract: Except for some U.S. states and localities, gay men and lesbians are largely unprotected from employment discrimination. In debate over national legislation (Employment Non-Discrimination Act), some legislators have questioned the efficacy of antidiscrimination legislation. To address this issue, we conducted three studies. In Study 1, we documented public awareness of sexual orientation employment antidiscrimination laws by contacting 111 households in areas that do and do not offer city-wide protective laws.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 81 publications
1
75
0
Order By: Relevance
“…Barron and Hebl (2013) observed that in areas with a larger lesbian/gay population, lesbian/gay applicants were treated more favorably than heterosexual ones (p ࣘ .05) while the opposite was true in areas with more conservative populations (p ࣘ .05). Lesbians were significantly disadvantaged in call-back rates compared to heterosexual women in socially conservative Munich, Germany (p ࣘ .05), but no such differences were detected in liberal Berlin (Weichselbaumer, 2015).…”
Section: Effect Of Local Characteristicsmentioning
confidence: 75%
See 4 more Smart Citations
“…Barron and Hebl (2013) observed that in areas with a larger lesbian/gay population, lesbian/gay applicants were treated more favorably than heterosexual ones (p ࣘ .05) while the opposite was true in areas with more conservative populations (p ࣘ .05). Lesbians were significantly disadvantaged in call-back rates compared to heterosexual women in socially conservative Munich, Germany (p ࣘ .05), but no such differences were detected in liberal Berlin (Weichselbaumer, 2015).…”
Section: Effect Of Local Characteristicsmentioning
confidence: 75%
“…Gorsuch (2014) presented the study as a real job task so the subjects were not aware that they were taking part in an experiment. Barron and Hebl (2013) manipulated subjects' beliefs on legality of employment discrimination against gay men and lesbians in a short training. The subjects then conducted a practice job interview with a researcher disguised as a gay/lesbian job candidate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations